Corrigendum to “Establishment and validation of LC-MS/MS technique for Lenacapavir quantification in rat plasma, with application to pharmacokinetic assessment” (Journal of Applied Pharmaceutical Science, 2025)
In the published article titled ‘Establishment and validation of LC-MS/MS technique for Lenacapavir quantification in rat plasma, with application to pharmacokinetic assessment’ which appeared in volume: 15, issue: 05 of the Journal of Applied Pharmaceutical Science [1], the one additional affiliation for Edward Raju Gope was missing. The correct affiliations and corresponding address is given below: Edward Raju Gope1,2*, Srikanth Pottendla1, Suneetha Yaparthi1 ¹Dr. Samuel George Institute of Pharmaceutical Sciences, Markapur, Andhra Pradesh, India. ²University College of Pharmaceutical Sciences, Acharya Nagarjuna University, Nagarjuna Nagar, Guntur, Andhra Pradesh, India. This correction applies to both the author affiliation section and the corresponding address. This corrigendum corrects all previous versions of the article.This is a correction to the following article:Gope ER, Pottendla S, Yaparthi S. Establishment and validation of LC-MS/MS technique for Lenacapavir quantification in rat plasma, with application to pharmacokinetic assessment. J Appl Pharm Sci. 2025;15(05):112–120. http://doi.org/10.7324/JAPS.2025.229006
Keywords: Corrigendum